Pharmacological studies of Neopicrorrhiza scrophularii-flora and its antidiabetic effect - Manandhar, Nayan (Journal of Nepal Pharmaceutical Association, 2015)
Neopicrorrhiza srophulariiflora (NS), locally known as “kutki / katuki” in nepali is available in 3500-4800 m of Nepal. The present study was carried out to evaluate the antidiabetic property of NS in streptozotocin (STZ) induced type 2 diabetic model rats. NS dried rhizomes, was extracted with 80% ethanol and water by cold percolation method. The extracts were administered at a dose of 1.25gkg-1 body weight for 21 consecutive days to type 2 diabetic male Long-Evans rats, bred at BIRDEM animal house. Serum glucose was estimated by GOD PAP method. Ethanol extract of N. srophulariiflora significantly (p